The immune role of the intestinal microbiome in knee osteoarthritis: a review of the possible mechanisms and therapies - Sun, Chang; Zhou, Xing; Guo, Ting; Meng, Jia (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a chronic degenerative joint disease characterized by cartilage damage and synovial inflammation and carries an enormous public health and economic burden. It is crucial to uncover the potential mechanisms of OA pathogenesis to develop new targets for OA treatment. In recent years, the pathogenic role of the gut microbiota in OA has been well recognized. Gut microbiota dysbiosis can break host-gut microbe equilibrium, trigger host immune responses and activate the “gut-joint axis”, which aggravates OA. However, although the role of the gut microbiota in OA is well known, the mechanisms modulating the interactions between the gut microbiota and host immunity remain unclear. This review summarizes research on the gut microbiota and the involved immune cells in OA and interprets the potential mechanisms for the interactions between the gut microbiota and host immune responses from four aspects: gut barrier, innate immunity, adaptive immunity and gut microbiota modulation. Future research should focus on the specific pathogen or the specific changes in the gut microbiota composition to identify the related signalling pathways involved in the pathogenesis of OA. In addition, future studies should include more novel interventions on immune cell modifications and gene regulation of specific gut microbiota related to OA to validate the application of gut microbiota modulation in the onset of OA.